1994
DOI: 10.1007/bf02540578
|View full text |Cite
|
Sign up to set email alerts
|

Technological and economical aspects of the metathesis of unsaturated esters

Abstract: The metathesis of alkenes is a well‐established reaction that is applied in various commercial processes. The meta‐thesis of functionalized olefins has not yet been commercialized despite its considerable potential. The conversion of oleochemical feedstocks into specialty chemicals appears especially attractive. In this paper, a process scheme is proposed for the production of 1,18‐dimethyl octadecanedioate from pure methyl oleate by metathesis. The chemical and technological bottlenecks are explored, and a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Thanks to its acidity, this system can be used in the reactions of Beckmann rearrangement [4][5][6][7][8][9][10], alcohol dehydration [11][12][13][14], partial oxidation of olefins [15][16][17][18][19], cracking [20][21][22][23], isomerization of hydrocarbons [24,25] and toluene disproportionation [25,26]. On the other hand, this system proved to be an effective support of metallic phase active in a number of reactions important for industry, like in the reactions of metathesis where it was a support of rhenium [27,28], cyclohexene hydrogenation, where it was a support of platinum [29] or carbon oxide hydrogenation as a support of ruthenium [30]. The versatile character and multifunctional applications of this support are related to its specific acidic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to its acidity, this system can be used in the reactions of Beckmann rearrangement [4][5][6][7][8][9][10], alcohol dehydration [11][12][13][14], partial oxidation of olefins [15][16][17][18][19], cracking [20][21][22][23], isomerization of hydrocarbons [24,25] and toluene disproportionation [25,26]. On the other hand, this system proved to be an effective support of metallic phase active in a number of reactions important for industry, like in the reactions of metathesis where it was a support of rhenium [27,28], cyclohexene hydrogenation, where it was a support of platinum [29] or carbon oxide hydrogenation as a support of ruthenium [30]. The versatile character and multifunctional applications of this support are related to its specific acidic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Olefin metathesis of seed oils and their fatty acid methyl esters has been an active area of research for greater than 25 years, with the breakthrough discovery by Mol that supported Re catalysts, activated with tetraalkyltin species, are active in the homometathesis of methyl oleate . This advance led to considerable activity in the development of heterogeneous metathesis catalysts focusing on new catalytic materials, improved activators, and fundamental surface science studies to understand the nature of the catalytically active site. , However, to date, the highest reported catalyst turnovers for the metathesis of methyl oleate with these heterogeneous catalysts is 900, due to severe catalyst sensitivity to polar impurities and polar functionality and inherently rapid deactivation pathways …”
Section: Introductionmentioning
confidence: 99%
“…This system provided turnover numbers (TON) of 166 for the self-metathesis of 1 after 90 min of reaction time, in comparison to a TON of 32 when the same catalyst without B 2 O 3 modification was studied. The technological aspects considering the use of a heterogeneous catalyst for the selfmetathesis of 1 were also discussed focusing on the design of a process and the potentials of a commercial application of such a process [34]. This study revealed that the bottleneck for commercialization of metathesis of methyl oleate was, at that time, the lack of a stable and sufficiently active catalysts.…”
Section: Self-metathesis Of Unsaturated Oleochemicalsmentioning
confidence: 99%